Biomolecular hydration in protein-protein interaction, protein stability and aggregation and lead optimization : computational studies - Mohan Rajan Pradhan (2017)
The role of intracellular water in biomolecular function is well recognized and yet quantifying this is challenging. This is largely because protein hydration is extremely sensitive to the protein surface chemistry and topology and also to the environmental conditions. This makes protein hydration dependent on the protein being studied, and so it is hard to formulate general rule of how water affects protein function. There is no single theory that describes the precise nature of the microscopic role of water in protein structure stability, interaction, dynamics and function. Interrogating this, in my PhD I have focused on (1) Developing hypotheses/algorithms/programs of biomolecular hydration and (2) Using these to probe the role of water in protein function. After providing a brief overview of biomolecular hydration and outlining the need for new insights to explain experimental observations such as aggregation (Chapter 1), a hydration metric is identified that is linked to Aggregation Prone Regions (APRs) in proteins. This hydration feature can provide guidance to complement existing strategies designed to inhibit protein aggregation (Chapter 2). Subsequently, I apply this feature to understand the loss of function through aggregation in the tumor suppressor protein p53 (Chapter 3), which allows us to model initial conformational events leading to the exposure of an aggregation prone region in p53 that could initiate the onset of aggregation. This also led to the identification of a novel "druggable‟ pocket in p53. Driven by the observation that restoring the wild type function of mutant p53 is known to prevent tumors, I am in the process of screening libraries of compounds against this new pocket to identify binders that may guide the development of molecules to restabilize mutant p53. During the course of exploring the hydration dynamics of proteins, I realized the need for a comprehensive, free, rapid and easy to use software package for characterizing hydration properties in a structural ensemble of a protein as derived from molecular dynamics simulation, for which a comprehensive software package, termed as "JAL‟, is developed (Chapter 4). "JAL‟ provides 3 novel utilities that have not yet been reported in other software packages: (1) computation of residence times of waters which are then used to rapidly identify water bridges involving multiple waters (2) rapid computation of buried waters in an explicit solvent MD trajectory using a novel “evaporation” technique and (3) a structure based search to compute the likelihood of favorably displacing interfacial waters; this method contrasts well with other available sophisticated but computationally expensive free energy methods. During the process of drug discovery, the question of which waters that exist in a binding site need to be displaced by the designed ligand is of critical importance and as yet has no universal solution. The utility of „JAL‟ is demonstrated using case studies of 4 proteins for which a variety of relevant experimental data is available: the DNA Binding Domain of the transcription factor p53, the translation initiation factor eIF4E, Scytalone dehydratase which catalyzes the biosynthesis of melanin, and the kinase domain of the signaling protein EGFR. One of these proteins, eIF4E, is highly hydrated in its nucleotide binding pocket as is seen in several crystal structures, and presented us with a good opportunity to explore the importance of these water molecules using „JAL‟ (Chapter 5). Combining systematic data mining and quantification of these hydration sites using „JAL‟ a novel two water-bridge motif is identified that appears to be central to the nucleotide recognition by eIF4E. This is a novel finding and I believe will facilitate the design of specific inhibitors of eIF4E which is a therapeutic target in oncology. Finally, I summarize and critique the work and discuss possible future directions (Chapter 6).